The Influence Of Entrepreneurship Education, Motivation, And Social Media On Entrepreneurship Interests Of Management Students At Panca Budi Development University Medan - Virna Rapenia; Roro Rian Agustin; Dian Septiana Sari (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of entrepreneurship education, motivation, and social media on entrepreneurial interest in management students at the Panca Budi University, Medan. The population in this study consisted of 50 3rd and 5th semester students of the Management study program with a concentration in digital business from 357 active management students with all concentrations in management, with a sample of 50 respondents, the sampling technique used was a saturated sample. This study was conducted in 2025-2026, using a questionnaire to collect quantitative primary data, which were then analyzed by multiple linear regression through SPSS. The results of the analysis showed that the variables of entrepreneurship education 0.002 <0.05, motivation 0.000 <0.05, and social media 0.009 <0.05 individually had a positive and significant influence on entrepreneurial interest. The F test showed a value of 95.655 (sig. 0.000), which supports that simultaneously, the three variables influence the entrepreneurial interest of management students at the Panca Budi University, Medan. The Adjusted R Square value is 0.853, this shows that the third variable contributes 85.3% to entrepreneurial interest.